The Possible Role of MOPr-DOPr Heteromers and Its Regulatory Protein RTP4 at Sensory Neurons in Relation to Pain Perception - Fujita, Wakako (Frontiers in Cellular Neuroscience, 2020)
Heteromers between mu opioid receptor (MOPr) and delta opioid receptor (DOPr) (i.e., MOPr-DOPr heteromer) have been found to be expressed in different brain regions, in the spinal cord, and in dorsal root ganglia. Recent studies on this heteromer reveal its important pathophysiological function in pain regulation including neuropathic pain; this suggests a role as a novel therapeutic target in chronic pain management. In addition, receptor transporter protein 4 (RTP4) has been shown to be involved in the intracellular maturation of the MOPr-DOPr heteromers. RTP4 appears to have unique distribution in vivo being highly expressed in sensory neurons and also macrophages; the latter are effector cells of the innate immune system that phagocytose foreign substances and secrete both pro-inflammatory and antimicrobial mediators; this suggests a possible contribution of RTP4 to neuronal immune-related pathological conditions such as neuropathic pain. Although RTP4 could be considered as an important therapeutic target in the management of pain via MOPr-DOPr heteromer, a few reports have supported this. This review will summarize the possible role or functions of the MOPr-DOPr heteromer and its regulatory molecule RTP4 in pain modulation at sensory neurons.